THE ROLE OF THE TAX BAILIFFS IN TAX COLLECTION IN INDONESIA - Anis Wahyu Hermawan (Journal of Tax Law and Policy, 2022)
There have been numerous tax regulations in Indonesia that strengthen tax collection; however, recent findings from the Financial Audit Agency and the amount of Uncollectible Tax Receivables from 2017 to 2021 remain quite high, exceeding 50% of gross tax receivables. Using multiple linear regression analysis, this study constructs six conclusions.